Morphometry, Bite-Force, and Paleobiology of the Late Miocene Caiman Purussaurus brasiliensis - Aureliano, Tito; Ghilardi, Aline M.; Guilherme, Edson; Souza-Filho, Jonas P.; Cavalcanti, Mauro; Riff, Douglas (PLOS ONE, 2015)
Purussaurus brasiliensis thrived in the northwestern portion of South America during the Late Miocene. Although substantial material has been recovered since its early discovery, this fossil crocodilian can still be considered as very poorly understood. In the present work, we used regression equations based on modern crocodilians to present novel details about the morphometry, bite-force and paleobiology of this species. According to our results, an adult Purussaurus brasiliensis was estimated to reach around 12.5 m in length, weighing around 8.4 metric tons, with a mean daily food intake of 40.6 kg. It was capable of generating sustained bite forces of 69,000 N (around 7 metric tons-force). The extreme size and strength reached by this animal seems to have allowed it to include a wide range of prey in its diet, making it a top predator in its ecosystem. As an adult, it would have preyed upon large to very large vertebrates, and, being unmatched by any other carnivore, it avoided competition. The evolution of a large body size granted P. brasiliensis many advantages, but it may also have led to its vulnerability. The constantly changing environment on a large geological scale may have reduced its long-term survival, favoring smaller species more resilient to ecological shifts.